Carbon nanotube-based stimuli-responsive nanocarriers for drug delivery. Issue 86 (31st August 2016) - Bafkary, R.; Khoee, S.
Abstract : In cancer therapy, smart nanocarriers are one of the most important nanoscale vectors of therapeutic agents. Abstract : In cancer therapy, smart nanocarriers are one of the most important nanoscale vectors of therapeutic agents. In this study, magnetic carbon nanotubes are functionalized with stimuli-responsive polymeric shells, which have thermal sensitivity and redox sensitivity due to the presence of PNIPAM- co -PHEMA and disulfide bonds, respectively. The chemical–physical properties of the nanovectors have been specified and used in a pinpointed DOX delivery system. At 25 °C, 12% of DOX was released from poly(NIPAM-HEMA-SS)/MN-MWCNTs in 12 h; as the temperature increased to 41 °C, the cumulative release amount of DOX in 12 h increased to 41%. Moreover, it was shown that in the presence of DTT, a more rapid release rate of DOX was observed. The in vitro hemolysis and in vivo biochemical analysis results revealed negligible toxicity of poly(NIPAM-HEMA-SS)/MN-MWCNTs in mice at a high dosage in the course of a 10 day experiment. The temperature responsive cytotoxicity of DOX–poly(NIPAM-HEMA-SS)/MN-MWCNTs was determined in vitro . In addition, with increasing temperature, the viability significantly decreased; the cell survival ratio was reduced from 59% ± 1% at 37 °C to 50% ± 2% at 41 °C at a concentration of 2 μg mL −1 because of the increased drug release under these conditions, likely as it was observed during in vitro drug release.